2006
DOI: 10.1021/ja061508q
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects in the Hydrosilylation of Coordinated Dinitrogen in a Ditantalum Complex:  Cleavage and Functionalization of N2

Abstract: The dinitrogen complex ([NPN]Ta)2(mu-eta1:eta2-N2)(mu-H)2, 1, (where [NPN] = (PhNSiMe2CH2)2PPh) undergoes hydrosilylation with primary and secondary alkyl- and arylsilanes, giving a new N-Si bond and a new terminal tantalum hydride derived from one Si-H unit. Various primary silanes can be employed to give isolable complexes of the general formula ([NPN]TaH)(mu-N-N-SiH(n)R(3-n))(mu-H)2(Ta[NPN]) (5, R=Bu, n = 2; 9, R=Ph, n = 2). Analogous complexes featuring secondary silanes are not isolable, because these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 44 publications
(100 reference statements)
1
72
1
Order By: Relevance
“…Subsequent treatment with boranes, silanes, and zirconium hydrides resulted in NÀN bond cleavage of the coordinated N 2 molecule. [16,17] For 2, the cleavage proceeded spontaneously and did not require external reducing agent. This process corresponds to an overall six-electron reduction of N 2 , in which two electrons are initially stored in a metal-metal bond, and four additional electrons are provided by H 2 elimination.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent treatment with boranes, silanes, and zirconium hydrides resulted in NÀN bond cleavage of the coordinated N 2 molecule. [16,17] For 2, the cleavage proceeded spontaneously and did not require external reducing agent. This process corresponds to an overall six-electron reduction of N 2 , in which two electrons are initially stored in a metal-metal bond, and four additional electrons are provided by H 2 elimination.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, this potential catalytic cycle was not realized, but in the process of this investigation, the extraordinary reactivity of 13.3 with E-H reagents was revealed. For example, we have reported that 13.3 is capable of undergoing hydroboration [68,69], hydroalumination [70], hydrosilylation [71][72][73] and zirconocene insertion [74] reactions, all of which result in new nitrogen-element (N-E) bond formation [44,67]. An overview of the reactivity of 13.3 towards these reagents is illustrated in Scheme 14.…”
Section: Tantalummentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] Removal of dihydrogen (H 2 ) through oxidation leads one to think about the "peroxycarbene" 4. Although likely not persistent, its valence tautomers (structures 5-7) begin to resemble heteroatom-functionalized architectures of tricyclic-fused natural products and promise both interesting structures and chemistry.…”
mentioning
confidence: 99%